(untitled) (Indian Journal of Animal Production and Management, 2013)
The present investigation was conducted on 301 Murrah buffaloes maintained at Buffalo Research center, Department of Livestock Production and Management, CCS Haryana Agricultural University, Hisar (India) with the main objective to study the effect of non-genetic factors affecting life time production traits in Murrah buffaloes. The overall least-squares means for Life time milk yield (LTMY), herd life [HL], productive life [PL], total number of days in milk [ND] and milk yield per day of productive life [MY/PL] were found to be 6722.43 ± 199.4 kg, 2795.19 ± 34.21 days, 1320.82 ± 31.44 days, 1011.57 ± 40.40 days and 4.66 ± 0.82 kg, respectively. The period of calving affected significantly all the life time performance traits. The weight group also affected significantly all the life time performance traits except number of days in milk (ND).